Nursing Care Report for Child by H With BBLSR at PKU Muhammadiyah Hospital Yogyakarta - Rosmaida Uli Handayani Siregar; Siti Arifah (International Journal of Health Engineering and Technology, 2025)
Very Low Birth Weight (VLBW) infants, those weighing less than 1,500 grams, face a high risk of complications such as respiratory distress, infections, and thermoregulatory instability due to organ immaturity. This condition necessitates intensive, comprehensive nursing care in a Neonatal Intensive Care Unit (NICU). Objective: This study aims to systematically describe the nursing care process provided to a premature infant with VLBW to illustrate the application of evidence-based practice. Methods: A descriptive qualitative case study design was used. The population included all VLBW infants at the NICU of An Ni’mah Hospital, PKU Muhammadiyah Yogyakarta, with a single case (infant By. H) selected as the sample. Data were collected through direct observation, interviews, and documentation studies. Data analysis followed the nursing process steps: assessment, diagnosis, planning, implementation, and evaluation. Results: Infant By. H, with a birth weight of 1350 grams, presented with four primary nursing diagnoses: ineffective breathing pattern, nutritional deficit, risk of infection, and ineffective thermoregulation. Conclusion: The systematic and collaborative nursing interventions proved effective in stabilizing the infant's clinical condition, as evidenced by improved respiratory function, significant weight gain, stable body temperature, and the absence of new infections. This case highlights the vital role of nurses in neonatal care and serves as a valuable learning tool.